Pembaharuan Hukum dalam Transaksi Asuransi pada Marketplace Asuransi Online di Indonesia - Anugerah, Fiqqih; Nurlaily, Nurlaily; Seroja, Triana Dewi (Universitas Batanghari Jambi, 2025)
The phenomenon of personal data misuse has become increasingly prevalent in today's society. Data breach cases in Indonesia are common due to weak regulations specifically designed to protect the personal data of online marketplace users. This study aims to investigate and analyze the phenomenon and implications of the development of insurance transactions within the scope of online marketplaces in Indonesia, as well as to provide recommendations for legal improvements or enhancements that are appropriate and can support healthy growth in Indonesia's online insurance industry. This research employs a normative legal approach by utilizing library research techniques to examine various guidelines. Secondary data collected through library research were analyzed using a qualitative juridical approach. The study is also supported by primary legal materials such as legislation. The findings of this study indicate that insurance agreements can be utilized to protect the confidentiality of personal data, ensure the certainty and security of transactions, and minimize the risks of digital transactions, such as fraud, delivery failures, and financial losses. Legal regulations related to online insurance marketplace businesses in Indonesia require adjustments and revisions to accommodate the rapid development of technology and e-commerce.